2018
DOI: 10.5194/gmd-2018-218
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

HOMMEXX 1.0: A Performance Portable Atmospheric Dynamical Core for the Energy Exascale Earth System Model

Abstract: Abstract. We present an architecture-portable and performant implementation of the atmospheric dynamical core (HOMME) of the Energy Exascale Earth System Model (E3SM). The original Fortran implementation is highly performant and scalable on conventional architectures using MPI and OpenMP. We rewrite the model in C++ and use the Kokkos library to express on-node parallelism in a largely architecture-independent implementation. Kokkos provides an abstraction of a compute node or device, layout-polymorphic multid… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…A smaller number of nodes shows much better agreement with the ideal scaling, which highlights a loss of efficiency when running in a higher throughput regime. This is consistent with the results of (Bertagna et al., 2019) who showed that Cori‐KNL efficiency can vary with the amount of workload per node.…”
Section: Resultssupporting
confidence: 93%
“…A smaller number of nodes shows much better agreement with the ideal scaling, which highlights a loss of efficiency when running in a higher throughput regime. This is consistent with the results of (Bertagna et al., 2019) who showed that Cori‐KNL efficiency can vary with the amount of workload per node.…”
Section: Resultssupporting
confidence: 93%
“…In addition, performance and portability across multiple architectures with a single source code requires NWP models to shift to domain-specific-language (DSL)-based approaches, such as Kokkos (Bertagna et al, 2019), Psyclone (Adams et al, 2019), and Stella/GridTools (Fuhrer et al, 2014; Thaler et al, 2019). Fault tolerance efforts requiring code modifications will more naturally interface with DSLs, see Section 3.3.4 in this paper for an example.…”
Section: Discussionmentioning
confidence: 99%
“…Kokkos (Bertagna et al, 2019) is a C++ library designed as a performance-portable node-parallel programming model to allow platform-independent parallel implementations across multiple heterogeneous architectures. The main idea of resilient Kokkos is extending the abstraction of parallel computation and data representation to support redundancy.…”
Section: Resilience Methodologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they lack in general functionality required for the specific domain of weather and climate, like 3D domains and a special treatment of the vertical dimension. Kokkos [5] provides a performance portable model for many core devices which has been demonstrated on the E3SM model [1]. The programming model contains useful parallel loop constructs and data layout abstractions.…”
Section: Related Workmentioning
confidence: 99%